Flame-retardant coating and preparation method thereof, flame-retardant coating, composite board and preparation method thereof

By using a combination of functionalized inorganic nanosheets, polymer main agent and cross-linking agent in flame retardant coatings, a dense flame retardant layer is formed, which solves the problems of existing flame retardants producing toxic smoke and reducing the mechanical properties of materials, and achieves It has good flame retardant and mechanical properties, and has environmental protection characteristics.

CN119331466APending Publication Date: 2025-01-21HEFEI MIDEA REFRIGERATOR CO LTD +3
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310914025.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing flame retardants produce toxic fumes and gases when burned and may reduce the mechanical properties of the material and cause bioenrichment problems, affecting the environment and human health.

Method used

Functionalized inorganic nanosheets are used as flame retardants. By combining with the main polymer agent and cross-linking agent, a dense flame retardant layer is formed, blocking oxygen transfer and the overflow of thermal cracking components, and significantly reducing peak heat release.

Benefits of technology

It achieves good flame retardant properties and mechanical properties, while avoiding the generation of toxic smoke, improving the fire safety performance of the material, and having environmentally friendly and green characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331466A_ABST
    Figure CN119331466A_ABST
Patent Text Reader

Abstract

The invention provides a flame-retardant coating and a preparation method thereof, a flame-retardant coating, a composite board and a preparation method thereof. The flame retardant coating includes: a polymer host; a cross-linking agent; the flame retardant is a functional inorganic nanosheet; and a dispersion medium. The functional inorganic nanosheets have a good physical barrier effect, transmission of oxygen and overflow of developing thermal cracking components can be effectively blocked by adding the functional inorganic nanosheets, then good flame retardant performance is achieved, after a flame-retardant coating is prepared from the coating, functional boron nitride can be gathered on the surface of a polymer main agent during combustion, and therefore the flame retardant performance of the coating is improved. According to the flame-retardant coating disclosed by the invention, a compact flame-retardant layer is formed, a base material in the flame-retardant coating is protected, peak heat release of the flame-retardant coating is remarkably reduced, and a good flame-retardant effect is realized; the functionalized inorganic nanosheets have good dimensional stability, corrosion resistance, oxidation resistance and thermal conductivity of boron nitride, so that the functionalized inorganic nanosheets can also improve the mechanical properties of the flame-retardant coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a functional flame retardant coating and a preparation method thereof, a flame retardant coating, a composite plate and a preparation method thereof. Background Art

[0002] Although the popular use of polymer materials has facilitated people's lives, due to their inherent flammability, they have become a major fire hazard in modern society. Therefore, it is urgent to improve their fire safety performance. Although traditional halogen flame retardants have been proven to have excellent flame retardant effects, they (especially bromine antimony flame retardants) produce a large amount of toxic and deadly smoke and gas when burned, and these smoke and gas diffuse very quickly, which has become one of the most important factors causing casualties in fires. In addition, the method of adding small molecule flame retardants not only makes the recycling of polymers difficult, but also may reduce the mechanical properties of the material. Small molecule flame retardants also have a tendency to gradually disperse into the environment as the base material decomposes, which usually brings potential bioaccumulation problems and poses a threat to people's health (especially for halogen-containing flame retardants). Therefore, there are still many technical problems with the common flame retardants at present. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a flame retardant coating having good flame retardant properties.

[0004] In the first aspect of the present invention, the present invention provides a flame retardant coating. According to an embodiment of the present invention, the flame retardant coating comprises: a polymer main agent; a cross-linking agent; a flame retardant, wherein the flame retardant is a functionalized inorganic nanosheet; and a dispersion medium. Thus, the functionalized inorganic nanosheet has a good physical barrier effect. The addition of the functionalized inorganic nanosheet can effectively block the transfer of oxygen and the overflow of volatile pyrolysis components, thereby achieving good flame retardant properties. When the flame retardant coating is prepared from the coating, the functionalized boron nitride can be gathered on the surface of the polymer main agent during combustion to form a dense flame retardant layer, protecting the substrate inside the flame retardant coating, significantly reducing the peak heat release (PHRR) of the flame retardant coating, and achieving a good flame retardant effect; at the same time, the functionalized inorganic nanosheet has the good dimensional stability, corrosion resistance and oxidation resistance of the inorganic material it contains.

[0005] According to an embodiment of the present invention, the polymer main agent is polyvinyl alcohol, the cross-linking agent is tannic acid, and the dispersion medium is water and ethanol.

[0006] According to an embodiment of the present invention, the solid content of the flame retardant coating is 50-60 mg / g.

[0007] According to an embodiment of the present invention, based on the total mass of solids in the flame retardant coating, the flame retardant coating includes, by mass percentage: 40% to 50% of the polymer main agent; 20% to 30% of the cross-linking agent; 20% to 30% of the functionalized inorganic nanosheets, and optionally, the dispersion medium is water and ethanol in a volume ratio of 1: (0.5 to 1.5).

[0008] According to an embodiment of the present invention, the functionalized inorganic nanosheets are tannic acid-modified inorganic nanosheets.

[0009] According to an embodiment of the present invention, the functionalized inorganic nanosheet has a planar size of 0.2 to 2 μm and a thickness of 5 to 20 nm.

[0010] According to an embodiment of the present invention, the inorganic material in the functionalized inorganic nanosheets is at least one of boron nitride, expanded graphite and mica.

[0011] According to an embodiment of the present invention, the boron nitride is hexagonal boron nitride.

[0012] In the second aspect of the present invention, the present invention provides a method for preparing the flame retardant coating described above. According to an embodiment of the present invention, the method for preparing the flame retardant coating comprises: adding a polymer main agent and a cross-linking agent to a dispersion medium respectively to obtain a mixed solution; gradually adding functionalized inorganic nanosheets to the mixed solution, and stirring evenly at a predetermined temperature to obtain the flame retardant coating. Thus, the functionalized inorganic nanosheets prepared by the above method have a good physical barrier effect. The addition of the functionalized inorganic nanosheets can effectively block the transfer of oxygen and the overflow of the volatile thermal decomposition components, thereby achieving good flame retardant properties. When the flame retardant coating is prepared by the coating, the functionalized boron nitride can be gathered on the surface of the polymer main agent during combustion, forming a dense flame retardant layer, protecting the substrate inside the flame retardant coating, significantly reducing the peak heat release (PHRR) of the flame retardant coating, and achieving a good flame retardant effect; at the same time, the inorganic nanosheets have good dimensional stability, corrosion resistance and oxidation resistance.

[0013] According to an embodiment of the present invention, the predetermined temperature is 70°C to 90°C.

[0014] According to an embodiment of the present invention, the preparation method of the functionalized inorganic nanosheets includes: uniformly mixing an inorganic material and tannic acid and ball-milling for a predetermined time to obtain a ball-milled mixture; adding a dispersant to the ball-milled mixture to obtain a dispersion; ultrasonically subjecting the dispersion to centrifugation, washing, and drying to obtain the functionalized inorganic nanosheets.

[0015] According to an embodiment of the present invention, the mass ratio of the boron nitride to the tannic acid is 1:(1.5-2), and optionally, the predetermined time is 8-10 hours.

[0016] In the third aspect of the present invention, the present invention provides a flame retardant coating. According to an embodiment of the present invention, the flame retardant coating is prepared by the flame retardant coating described above. As a result, the flame retardant coating has good flame retardant properties and better mechanical properties. Those skilled in the art can understand that the flame retardant coating has all the characteristics and advantages of the flame retardant coating described above, and no more details are given here.

[0017] According to an embodiment of the present invention, the thickness of the flame retardant coating is 50-400 μm.

[0018] In a fourth aspect of the present invention, the present invention provides a composite board. According to an embodiment of the present invention, the composite board comprises: a substrate; and the flame retardant coating described above, wherein the flame retardant coating is disposed on at least one surface of the substrate, and optionally, the substrate is at least one of polyurethane foam, wood board and polyvinyl chloride board. Thus, the flame retardant coating in the composite board has good flame retardant properties, can well protect the substrate, and thus improve the flame retardant properties of the composite board.

[0019] In the fifth aspect of the present invention, the present invention provides a method for preparing the aforementioned composite board. According to an embodiment of the present invention, the method for preparing the composite board comprises: coating the aforementioned flame retardant coating on at least one surface of a substrate; curing the flame retardant coating at a set temperature to obtain the composite board, and optionally, the set temperature is 35°C to 55°C. As a result, the flame retardant coating in the composite board has good flame retardant properties, can well protect the substrate, and thus improve the flame retardant properties of the composite board. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0021] Figure 1 These are the dispersion photos of functionalized boron nitride, functionalized expandable graphite and functionalized mica in water, transmission electron microscope photos and photos of functionalized boron nitride after film formation;

[0022] Figure 2 It is a schematic diagram of the principle of tannic acid-assisted mechanical ball milling exfoliation and modification of hexagonal boron nitride in the present invention;

[0023] Figure 3 This is a schematic diagram of the principle of the hydrogen bond self-assembly process during solvent evaporation;

[0024] Figure 4 It is a schematic diagram of a process for preparing a flame retardant coating in one embodiment of the present invention;

[0025] Figure 5 This is a scanning electron microscope image of the hexagonal boron nitride raw material;

[0026] Figure 6 is a scanning electron microscope image of the functionalized boron nitride nanosheet (TA-BNNS-2) prepared in Example 2;

[0027] Figure 7 It is the infrared (IR) spectra of the raw materials boron nitride (h-BN) and tannic acid (Tannic Acid) in Examples 1 to 3 and the functionalized boron nitride nanosheet (TA-BNNS-2) obtained in Example 2;

[0028] Figure 8 It is a thermogravimetric (TG) test graph of the raw materials boron nitride (h-BN) and tannic acid (Tannic Acid) in Examples 1 to 3 and the functionalized boron nitride nanosheet (TA-BNNS-2) obtained in Example 2;

[0029] Fig. 9 The thermogravimetric (TG) graphs and corresponding differential thermogravimetric analysis (DTG) graphs of the pure PVA sample, PVA-TA coating, PVA-TA@BNNS coating in Example 4 and the PVA-TA-RPUF coating in Comparative Example 1;

[0030] Fig.10 The peak heat release (HRR) data and the total heat release (THR) data of the cone calorimeter tested in Examples 5 to 7 and Comparative Example 1;

[0031] Fig.11 It is an SEM image of the carbon layer of pure polyurethane rigid foam after the flame retardancy test and an SEM image of the carbon layer of the flame retardant polyurethane rigid foam prepared in Example 7 after the flame retardancy test. DETAILED DESCRIPTION

[0032] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0033] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0034] In the first aspect of the present invention, the present invention provides a flame retardant coating. According to an embodiment of the present invention, the flame retardant coating includes: a polymer main agent; a cross-linking agent; a flame retardant, wherein the flame retardant is a functionalized inorganic nanosheet; and a dispersion medium. As a result, the functionalized inorganic nanosheet has a good physical barrier effect. The addition of the functionalized inorganic nanosheet can effectively block the transfer of oxygen and the overflow of volatile pyrolysis components, thereby achieving good flame retardant properties. When the flame retardant coating is prepared from the coating, the functionalized inorganic nanosheet can be gathered on the surface of the polymer main agent during combustion to form a dense flame retardant layer, protecting the substrate inside the flame retardant coating, significantly reducing the peak heat release (PHRR) of the flame retardant coating, and achieving a good flame retardant effect; at the same time, the functionalized inorganic nanosheet has the good dimensional stability, corrosion resistance, and antioxidant properties of the inorganic material it contains. The functionalized inorganic nanosheets have good chemical and thermal conductivity, so the functionalized inorganic nanosheets can also improve the mechanical properties of the flame retardant coating; in addition, the functionalized inorganic nanosheets used are functionalized inorganic nanosheets that are peeled off to a thickness of nanometers, which can make the functionalized inorganic nanosheets evenly dispersed in the flame retardant coating, that is, they can be evenly dispersed in the flame retardant coating with a higher concentration; at the same time, after the inorganic material is functionalized, the compatibility of its layered nanomaterials and polymer main agent can be effectively improved, thereby improving the mechanical properties and thermal properties of the polymer main agent / nanocomposite material (i.e., functionalized inorganic nanosheets), thereby improving the flame retardancy of the coating.

[0035] According to an embodiment of the present invention, the inorganic material in the functionalized inorganic nanosheet is at least one of boron nitride, expanded graphite and mica, and the above inorganic material has good dimensional stability, corrosion resistance, oxidation resistance and thermal conductivity. In some embodiments, the functionalized inorganic nanosheet is a functionalized boron nitride nanosheet, wherein the boron nitride is hexagonal boron nitride (h-BN). Hexagonal boron nitride has a crystal structure similar to that of graphite, and boron and nitrogen form hexagonal mesh layers that are stacked on each other; therefore, it can be peeled off by physical and chemical methods such as mechanical ball milling, ultrasound and small molecule intercalation to prepare nanosheets. Figure 1 The scanning electron microscope images of functionalized boron nitride, functionalized expandable graphite and functionalized mica in some embodiments are given in

[0036] According to an embodiment of the present invention, the functionalized inorganic nanosheets are inorganic nanosheets modified with tannic acid. Before modification, inorganic materials such as boron nitride, expanded graphite and mica have relatively thick sheets and almost no active groups on the surface, and cannot be directly used for compounding with polymers. In the present invention, a large number of hydroxyl groups are introduced into the functionalized inorganic nanosheets through the inorganic materials modified with tannic acid, thereby improving the dispersibility of the functionalized inorganic nanosheets in the dispersion medium, and can also better improve its compatibility with the polymer body, thereby better improving the mechanical properties and thermal properties of the flame retardant coating formed by the flame retardant coating, and further improving the flame retardant properties of the flame retardant coating, and the functionalized inorganic nanosheets will not lose the original chemical stability, thermal stability and oxidation resistance of the original inorganic material; in addition, when the inorganic material is hexagonal boron nitride, the use of tannic acid to modify the hexagonal boron nitride can also help the exfoliation of the hexagonal boron nitride to obtain a functionalized boron nitride with a nanosheet structure. Among them, the principle of tannic acid modification of hexagonal boron nitride is as follows: refer to Figure 2 The hydroxyl groups in tannic acid form hydrogen bonds with boron nitride, so that tannic acid can be firmly adsorbed on the surface of boron nitride, and a large number of hydroxyl and other modification groups are introduced into boron nitride, thereby improving the dispersibility of functionalized inorganic nanosheets in the dispersion medium, and at the same time improving its compatibility with the polymer main agent, thereby improving the mechanical properties and thermal properties of the polymer main agent / functionalized inorganic nanosheets, thereby improving the flame retardancy of the coating. Moreover, the addition of functionalized inorganic nanosheets can also improve the bonding strength and water resistance of the flame retardant coating, thereby improving the mechanical properties and water resistance of the flame retardant coating prepared therefrom. In addition, the principle of the modification of expanded graphite and mica by tannic acid is similar to the principle of the modification of hexagonal boron nitride, which will not be elaborated here.

[0037] According to an embodiment of the present invention, the planar size of the functionalized inorganic nanosheet is 0.2 to 2 μm (for example, 0.2 μm, 0.5 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2.0 μm), and the thickness is 5 to 20 nm (for example, 5 nm, 8 nm, 10 nm, 13 nm, 15 nm, 18 nm, 20 nm). The functionalized inorganic nanosheets of the nanosheet structure of the above size can be well and evenly dispersed in the dispersion medium, and the specific surface area of ​​the functionalized inorganic nanosheets of the above size is large, which can be more fully contacted with the polymer main agent and gathered on the surface of the polymer main agent, thereby better blocking the transmission of oxygen and the overflow of volatile thermal decomposition components, thereby effectively improving the flame retardant properties of the coating.

[0038] According to an embodiment of the present invention, the polymer main agent is polyvinyl alcohol (PVA), the cross-linking agent is tannic acid (TA), and the dispersion medium is water and ethanol. Figure 3 ( Figure 3Taking functionalized boron nitride as an example, a schematic diagram of the principle of the solvent evaporation hydrogen bond self-assembly process is shown in the figure. The hydrogen bond self-assembly characteristics of solvent evaporation can be used to dynamically adjust the crosslinking of hydrogen bonds between polyvinyl alcohol and tannic acid using water and ethanol, thereby achieving physical crosslinking. The flame retardant coating can be applied to the surface of the substrate in a simple one-step manner (such as dipping, brushing or spraying, etc.) without the need for additional crosslinking. In addition, polyvinyl alcohol and tannic acid are both biomass materials, and inorganic materials such as boron nitride, expanded graphite and mica have stable chemical properties and are biologically inert, thereby making the flame retardant coating of the present invention environmentally friendly and green.

[0039] According to an embodiment of the present invention, the solid content of the flame retardant coating is 50-60 mg / g, such as 50 mg / g, 51 mg / g, 52 mg / g, 53 mg / g, 54 mg / g, 55 mg / g, 56 mg / g, 57 mg / g, 58 mg / g, 59 mg / g, 60 mg / g, etc. The flame retardant coating with the above solid content is easy to cure and has a certain fluidity, which is easy to apply and can help to obtain a flame retardant coating with uniform thickness; if the solid content is low, the fluidity of the flame retardant coating is large, and the flame retardant coating is not easy to fix after coating, resulting in a thin coating thickness obtained by one coating, and the thickness uniformity is relatively poor; if the solid content is high, the fluidity of the flame retardant coating is low, and the thickness uniformity of the coating after coating and curing is relatively poor.

[0040] According to an embodiment of the present invention, based on the total mass of the solid in the flame retardant coating, the flame retardant coating includes, by mass percentage: 40% to 50% (such as 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%) of a polymer main agent; 20% to 30% (such as 20%, 21%, 22%, 23%, 24%, 5%, 26%, 27%, 28%, 29%, 30%) of a cross-linking agent; 20% to 30% (such as 20%, 21%, 22%, 23%, 24%, 5%, 26%, 27%, 28%, 29%, 30%) of functionalized inorganic nanosheets. The mechanical properties and thermal properties of the coating formed by the above-mentioned content components are both good, that is, the comprehensive performance of the prepared flame retardant coating is good, it has extremely high mechanical properties, and also meets its requirements for flame retardant properties.

[0041] Furthermore, in the flame retardant coating, the dispersion medium is water and ethanol in a volume ratio of 1: (0.5-1.5), for example, water and ethanol in a volume ratio of 1: 1. Water is the most commonly used solvent for polyvinyl alcohol. PVA has a high solubility in water and can meet the needs of preparing the coating, while PVA has a poor solubility in ethanol. Adding ethanol can weaken the hydrogen bonding between polyvinyl alcohol and tannic acid and prevent agglomeration.

[0042] In the second aspect of the present invention, the present invention provides a method for preparing the flame retardant coating as described above. Figure 4 , the method for preparing the flame retardant coating comprises:

[0043] S100: adding the polymer main agent and the cross-linking agent into the dispersion medium respectively to obtain a mixed solution.

[0044] In this step, the polymer main agent is polyvinyl alcohol (PVA), the cross-linking agent is tannic acid (TA), and the dispersion medium is water and ethanol. Figure 3 , the hydrogen bond self-assembly principle of solvent volatilization is adopted, and water and ethanol are used to dynamically adjust the cross-linking of hydrogen bonds between polyvinyl alcohol and tannic acid, thereby realizing physical cross-linking, and then the flame retardant coating can be simply coated on the surface of the substrate in one step (such as dipping, brushing or spraying, etc.) without the need for additional cross-linking; in addition, polyvinyl alcohol and tannic acid are both biomass materials, and inorganic materials such as boron nitride, expanded graphite and mica have stable chemical properties and are biologically inert, thereby making the flame retardant coating of the present invention and its preparation process environmentally friendly and green.

[0045] Among them, in some embodiments, the method of adding the polymer main agent and the cross-linking agent into the dispersion medium respectively includes: dissolving a certain mass of polyvinyl alcohol in water to obtain a polyvinyl alcohol solution of a certain concentration; adding a certain mass of tannic acid into ethanol, stirring until it is completely dissolved, to obtain an ethanol solution of tannic acid; under a certain temperature (such as 75-85°C) and stirring conditions, adding the ethanol solution of tannic acid dropwise into the polyvinyl alcohol aqueous solution, and stirring until the two solutions are completely and evenly dispersed.

[0046] S200: gradually adding the functionalized inorganic nanosheets into the mixed solution, and stirring evenly at a predetermined temperature to obtain a flame retardant coating.

[0047] According to some embodiments of the present invention, in this step, the predetermined temperature is 70°C to 90°C, such as 70°C, 72°C, 75°C, 78°C, 80°C, 83°C, 85°C, 88°C, 90°C, etc. At the above temperature, the functionalized inorganic nanosheets can be quickly and evenly dispersed into the mixed solution, and the hydrogen bond cross-linking between the polyvinyl alcohol, tannic acid and the functionalized inorganic nanosheets is promoted to obtain a flame retardant coating with stable properties.

[0048] According to some embodiments of the present invention, a method for preparing a functionalized inorganic nanosheet includes:

[0049] S210: The inorganic material and tannic acid are mixed uniformly and ball-milled for a predetermined time to obtain a ball-milled mixture. In this step, the inorganic material and tannic acid can be effectively contacted by ball milling, so that the tannic acid can fully modify the inorganic materials such as boron nitride, expanded graphite and mica to obtain functionalized inorganic nanosheets. That is, by modifying the inorganic materials such as boron nitride, expanded graphite and mica with tannic acid, a large number of hydroxyl groups are introduced into the functionalized inorganic nanosheets, thereby improving the dispersibility of the functionalized inorganic nanosheets in the dispersion medium, and can also better improve the compatibility between the functionalized inorganic nanosheets and the polymer body, thereby better improving the mechanical properties and thermal properties of the flame-retardant coating formed by the flame-retardant coating, and further improving the flame retardant properties of the flame-retardant coating. At the same time, ball milling is also helpful for the stripping of inorganic materials such as boron nitride, expanded graphite and mica.

[0050] In addition, the use of tannic acid to modify hexagonal boron nitride can also help the exfoliation of hexagonal boron nitride to obtain functionalized boron nitride with nanosheet structure. The principle of tannic acid modification of hexagonal boron nitride is as follows: Figure 2 , active sites such as defects are formed on the surface of boron nitride through mechanochemical methods, thereby realizing the modification of boron nitride by tannic acid. In addition, active groups such as hydroxyl groups can be introduced on the surface of boron nitride to improve the hydrophilicity and reactivity of boron nitride nanosheets, while improving its compatibility with the polymer main agent, thereby improving the mechanical properties and thermal properties of the polymer main agent / functionalized inorganic nanosheets, thereby improving the flame retardancy of the coating.

[0051] Among them, in some embodiments, the mass ratio of inorganic material to tannic acid is 1:(1.5~2), for example, the mass ratio of inorganic material to tannic acid is 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:2, etc. The above ratio allows tannic acid to fully modify inorganic materials such as boron nitride, expanded graphite and mica, while ensuring a high raw material utilization rate of tannic acid to avoid its waste.

[0052] Furthermore, the predetermined time of ball milling is 8 to 10 hours. In this way, the modification of inorganic materials such as boron nitride, expanded graphite and mica by tannic acid can be fully completed.

[0053] S220: adding a dispersant to the ball-milled mixture to obtain a dispersion. In this step, the dispersant may be water.

[0054] S230: ultrasonically, centrifugally, clean, and dry the dispersion to obtain the functionalized inorganic nanosheets. Ultrasound and centrifugation can effectively realize the stripping of inorganic materials to obtain functionalized inorganic nanosheets with nanosheet structures. At the same time, free tannic acid (tannic acid that is not hydrogen-bonded to inorganic materials) can also be removed during the centrifugation and cleaning process. In order to fully strip the inorganic materials, multiple ultrasonic and centrifugation processes can be performed until the supernatant is colorless and transparent to ensure that the inorganic materials are completely and fully stripped.

[0055] According to the embodiments of the present invention, no strong acid additive is required in the modification and stripping process of inorganic materials such as boron nitride, expanded graphite and mica. The modification and stripping of inorganic materials such as boron nitride, expanded graphite and mica can still be efficiently achieved, while improving environmental friendliness.

[0056] According to the embodiment of the present invention, the functionalized inorganic nanosheets prepared by the above method have good physical barrier effect. The addition of the functionalized inorganic nanosheets can effectively block the transfer of oxygen and the overflow of volatile pyrolysis components, thereby achieving good flame retardant performance. When the flame retardant coating is prepared from the coating, the functionalized inorganic nanosheets can be gathered on the surface of the polymer main agent during combustion to form a dense flame retardant layer, which protects the substrate inside the flame retardant coating and significantly reduces the peak heat release (PHRR) of the flame retardant coating, thereby achieving good flame retardant effect. At the same time, the functionalized inorganic nanosheets have the inorganic materials they contain. Good dimensional stability, corrosion resistance and oxidation resistance; in addition, functionalized inorganic nanosheets are used, that is, functionalized inorganic nanosheets that are peeled off to a thickness of nanometers, which can make the functionalized inorganic nanosheets evenly dispersed in the flame retardant coating, that is, they can be evenly dispersed in the flame retardant coating with a higher concentration; at the same time, after the functionalization of inorganic materials such as boron nitride, expanded graphite and mica, the compatibility of their layered nanomaterials and polymer main agents can be effectively improved, thereby improving the mechanical properties and thermal properties of the polymer main agent / nanocomposite material (that is, functionalized inorganic nanosheets), thereby improving the flame retardancy of the coating.

[0057] In the third aspect of the present invention, the present invention provides a flame retardant coating. According to an embodiment of the present invention, the flame retardant coating is prepared by the flame retardant coating described above. As a result, the flame retardant coating has good flame retardant properties and better mechanical properties. Those skilled in the art can understand that the flame retardant coating has all the characteristics and advantages of the flame retardant coating described above, and no more details are given here.

[0058] According to an embodiment of the present invention, the thickness of the flame retardant coating is 50 to 150 μm, such as 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, and 150 μm. The flame retardant coating of the above thickness can have good flame retardancy, mechanical properties, water resistance and other properties at the same time, meeting the use requirements of the flame retardant coating in different use environments.

[0059] In a fourth aspect of the present invention, the present invention provides a composite board. According to an embodiment of the present invention, the composite board includes: a substrate; and the flame retardant coating described above, the flame retardant coating being disposed on at least one surface of the substrate. Thus, the flame retardant coating in the composite board has good flame retardant properties, mechanical properties, water resistance, etc., can well protect the substrate, and thus improve the flame retardant properties of the composite board.

[0060] According to the embodiments of the present invention, there is no special requirement for the specific type of the substrate, and those skilled in the art can flexibly select according to actual needs. It can be seen that the flame retardant coating of the present invention has a wide range of applications and is not limited to a specific substrate material. In some embodiments, the substrate is at least one of polyurethane foam (HPUF), wood board, and polyvinyl chloride board (PVC).

[0061] In a fifth aspect of the present invention, the present invention provides a method for preparing the aforementioned composite board. According to an embodiment of the present invention, the method for preparing the composite board comprises:

[0062] S1000: Applying a flame retardant coating on at least one surface of a substrate.

[0063] There are no special requirements for the specific method of coating, and those skilled in the art can flexibly select according to the reagent conditions. In some embodiments, the specific process of coating can be dipping, brushing, spraying, spin coating and other process methods.

[0064] S2000: The flame retardant coating is cured at a set temperature to obtain a composite board. During the curing process, the ethanol in the dispersion medium evaporates first. After the ethanol evaporates, a strong hydrogen bond will be generated between the polyvinyl alcohol and tannic acid, thereby improving the density, structural stability and mechanical properties of the flame retardant coating.

[0065] Furthermore, in some embodiments, the set curing temperature is 35°C to 55°C, such as 35°C, 37°C, 40°C, 42°C, 45°C, 48°C, 50°C, 52°C, 55°C, etc. At the above curing temperatures, ethanol can evaporate first, and then water gradually evaporates. Therefore, the curing process is relatively gentle and not too rapid, thereby improving the quality of curing.

[0066] According to an embodiment of the present invention, the flame retardant coating in the composite board prepared by the above method has good flame retardant properties, can well protect the substrate, and thus improve the flame retardant properties of the composite board; moreover, the preparation method is simple, low in cost, and high in safety, which is conducive to achieving industrial mass production.

[0067] Example

[0068] Example 1

[0069] The method for preparing functionalized boron nitride nanosheets comprises:

[0070] (1) 4 g of hexagonal boron nitride (h-BN) powder with a size of about 30 μm and 8 g of tannic acid (TA) powder were mixed evenly and added to a ball mill made of agate, followed by adding agate ball mill beads (20 g, 1 mm in diameter and 60 g, 10 mm in diameter) for later use.

[0071] (2) A planetary ball mill was used at a rotation speed of 400 rpm for 8 hours to obtain a ball-milled mixture.

[0072] (3) After ball milling, about 60 g of deionized water was added to the ball-milled mixture of h-BN and TA, and ultrasonic stirring was performed to make it evenly dispersed. Then, centrifugation (speed 10000 rpm, time 5 min) was performed to remove free tannic acid. This step was repeated several times until the upper liquid after centrifugation was colorless and transparent.

[0073] (4) Finally, the precipitate obtained by centrifugation is dried to obtain functionalized boron nitride nanosheets (TA-BNNS-1).

[0074] Example 2

[0075] The method for preparing functionalized boron nitride nanosheets comprises:

[0076] (1) 4 g of hexagonal boron nitride powder with a size of about 30 μm and 8 g of tannic acid powder were mixed evenly and added to a ball mill made of agate, followed by adding agate ball mill beads (20 g of mass, 1 mm in diameter and 60 g of mass, 10 mm in diameter) for later use.

[0077] (2) A planetary ball mill was used at a rotation speed of 400 rpm for 9 hours to obtain a ball-milled mixture.

[0078] (3) After ball milling, about 60 g of deionized water was added to the ball-milled mixture of h-BN and TA, and ultrasonic stirring was performed to make it evenly dispersed. Then, centrifugation (speed 10000 rpm, time 5 min) was performed to remove free tannic acid. This step was repeated several times until the upper liquid after centrifugation was colorless and transparent.

[0079] (4) Finally, the precipitate obtained by centrifugation is dried to obtain functionalized boron nitride nanosheets (TA-BNNS-2).

[0080] Example 3

[0081] (1) 4 g of hexagonal boron nitride powder with a size of about 30 μm and 8 g of tannic acid powder were mixed evenly and added to a ball mill made of agate, followed by adding agate ball mill beads (20 g of mass, 1 mm in diameter and 60 g of mass, 10 mm in diameter) for later use.

[0082] (2) A planetary ball mill was used at a rotation speed of 400 rpm for 10 hours to obtain a ball-milled mixture.

[0083] (3) After ball milling, about 60 g of deionized water was added to the ball-milled mixture of h-BN and TA, and ultrasonic stirring was performed to make it evenly dispersed. Then, centrifugation (speed 10000 rpm, time 5 min) was performed to remove free tannic acid. This step was repeated several times until the upper liquid after centrifugation was colorless and transparent.

[0084] (4) Finally, the precipitate obtained by centrifugation is dried to obtain functionalized boron nitride nanosheets (TA-BNNS-3).

[0085] The raw materials used in Examples 1 to 3 are the same as bulk boron nitride (bulk-BN) and tannic acid (Tannic Acid). The scanning electron microscopy of hexagonal boron nitride can refer to Figure 5 ,Depend on Figure 5 It can be seen that the hexagonal boron nitride has a relatively thick layer before modification and exfoliation;

[0086] The SEM image of the functionalized boron nitride nanosheets (TA-BNNS-2) prepared in Example 2 can be found at Figure 6 ,Depend on Figure 6 It can be seen that the functionalized boron nitride was successfully exfoliated into nanostructures, i.e., functionalized boron nitride nanosheets were obtained;

[0087] The raw materials of boron nitride (h-BN) and tannic acid (Tannic Acid) and the functionalized boron nitride nanosheets (TA-BNNS) obtained in Example 2 were tested by infrared (IR) spectra. The test results can be found in Figure 7 ,Depend on Figure 7 It can be seen that the functionalized boron nitride nanosheets contain -OH and C=C in tannic acid and NH and BN in boron nitride, which means that tannic acid successfully modified hexagonal boron nitride and obtained tannic acid functionalized boron nitride nanosheets.

[0088] The raw materials of boron nitride (h-BN) and tannic acid (Tannic Acid) and the functionalized boron nitride nanosheets (TA-BNNS) obtained in Example 2 were subjected to thermogravimetric (TG) tests in a nitrogen atmosphere. The thermogravimetric test curves can be found in Figure 8 The results of thermogravimetric analysis further confirmed the successful modification of boron nitride by tannic acid.

[0089] Example 4

[0090] The preparation method of the flame retardant coating (PVA-TA@BNNS coating) and the flame retardant coating (PVA-TA@BNNS coating) includes:

[0091] (1) 12.75 g of polyvinyl alcohol (PVA-1788) was dissolved in 115 g of deionized water to prepare a 10% PVA aqueous solution. 6.375 g of tannic acid was added to 227.5 g of ethanol and stirred until completely dissolved.

[0092] (2) Under the condition of stirring in an oil bath at 80° C., the ethanol solution of tannic acid was added dropwise to the PVA aqueous solution, and stirring was continued for about 30 min until the solution was completely dispersed to obtain a PVA-TA mixed solution.

[0093] (3) 8.5 g of the modified TA-BNNS-2 obtained in Example 2 was added to 91.5 g of deionized water and ultrasonically stirred until the mixture was uniformly dispersed to obtain a BNNS aqueous dispersion.

[0094] (4) Under the condition of stirring in an oil bath at 80° C., the BNNS aqueous dispersion was added dropwise to the PVA-TA mixed solution in step (2), and stirring was continued for about 30 min until the mixture was uniformly dispersed, thereby obtaining the PVA-TA@BNNS coating.

[0095] (5) Take 8.33 g of the PVA-TA mixed solution prepared in step (2), put it into a polytetrafluoroethylene mold, and then put it into an oven at 40° C. until it is completely cured to obtain a PVA-TA coating.

[0096] (6) 8.33 g of the PVA-TA@BNNS coating prepared in step (4) was taken and placed into a polytetrafluoroethylene mold, and then placed in an oven at 40° C. until completely cured to obtain a flame-retardant PVA-TA@BNNS coating.

[0097] Thermogravimetric (TG) graphs and corresponding differential thermogravimetric (DTG) graphs were performed on pure PVA samples, PVA-TA coatings, and PVA-TA@BNNS coatings. The test results are shown in Fig. 9 ,Depend on Fig. 9It can be seen that in the thermogravimetric diagram of the PVA-TA@BNNS coating, weight loss begins at around 210°C, the component burned out in the range of 210°C to 310°C is mainly tannic acid TA, and the component burned out in the range of 300°C to 500°C is mainly PVA.

[0098] Example 5

[0099] The method for preparing a flame retardant coating (PVA-TA@BNNS coating) and a flame retardant polyurethane rigid foam (BN-RPUF for short) includes:

[0100] (1) 12.75 g of polyvinyl alcohol (PVA-1788) was dissolved in 115 g of deionized water to prepare a 10% PVA aqueous solution. 6.375 g of tannic acid was added to 227.5 g of ethanol and stirred until completely dissolved.

[0101] (2) Under the condition of stirring in an oil bath at 80° C., the ethanol solution of tannic acid was added dropwise to the PVA aqueous solution, and stirring was continued for about 30 min until the solution was completely dispersed to obtain a PVA-TA mixed solution.

[0102] (3) 8.5 g of the modified TA-BNNS-2 obtained in Example 2 was added to 91.5 g of deionized water and ultrasonically stirred until the mixture was uniformly dispersed to obtain a BNNS aqueous dispersion.

[0103] (4) Under the condition of stirring in an oil bath at 80° C., the BNNS aqueous dispersion was added dropwise to the PVA-TA mixed solution in step (2), and stirring was continued for about 30 min until the mixture was uniformly dispersed, thereby obtaining the PVA-TA@BNNS coating.

[0104] (5) After washing the rigid polyurethane foam (RPUF) with ethanol three times, drying and setting aside, 8.33 g of the PVA-TA@BNNS coating prepared in step (4) was applied to the surface of the RPUF, and then placed in an oven at 40° C. until completely cured, obtaining a coating coating amount per unit area of ​​50 g / m 2 Flame retardant polyurethane rigid foam (50-BN-RPUF).

[0105] Example 6

[0106] The method for preparing a flame retardant coating (PVA-TA@BNNS coating) and a flame retardant polyurethane rigid foam (BN-RPUF for short) includes:

[0107] (1) 12.75 g of polyvinyl alcohol (PVA-1788) was dissolved in 115 g of deionized water to prepare a 10% PVA aqueous solution. 6.375 g of tannic acid was added to 227.5 g of ethanol and stirred until completely dissolved.

[0108] (2) Under the condition of stirring in an oil bath at 80° C., the ethanol solution of tannic acid was added dropwise to the PVA aqueous solution, and stirring was continued for about 30 min until the solution was completely dispersed to obtain a PVA-TA mixed solution.

[0109] (3) 8.5 g of the modified TA-BNNS-2 obtained in Example 2 was added to 91.5 g of deionized water and ultrasonically stirred until the mixture was uniformly dispersed to obtain a BNNS aqueous dispersion.

[0110] (4) Under the condition of stirring in an oil bath at 80° C., the BNNS aqueous dispersion was added dropwise to the PVA-TA mixed solution in step (2), and stirring was continued for about 30 min until the mixture was uniformly dispersed, thereby obtaining the PVA-TA@BNNS coating.

[0111] (5) After washing the rigid polyurethane foam (RPUF) with ethanol three times, drying and setting aside, 16.67 g of the PVA-TA@BNNS coating prepared in step (4) was applied to the surface of the HPUF, and then placed in an oven at 40° C. until completely cured, obtaining a coating coating amount per unit area of ​​100 g / m 2 Flame retardant polyurethane rigid foam (100-BN-RPUF).

[0112] Example 7

[0113] The method for preparing a flame retardant coating (PVA-TA@BNNS coating) and a flame retardant polyurethane rigid foam (BN-RPUF for short) includes:

[0114] (1) 12.75 g of polyvinyl alcohol (PVA-1788) was dissolved in 115 g of deionized water to prepare a 10% PVA aqueous solution. 6.375 g of tannic acid was added to 227.5 g of ethanol and stirred until completely dissolved.

[0115] (2) Under the condition of stirring in an oil bath at 80° C., the ethanol solution of tannic acid was added dropwise to the PVA aqueous solution, and stirring was continued for about 30 min until the solution was completely dispersed to obtain a PVA-TA mixed solution.

[0116] (3) 8.5 g of the modified TA-BNNS-2 obtained in Example 2 was added to 91.5 g of deionized water and ultrasonically stirred until the mixture was uniformly dispersed to obtain a BNNS aqueous dispersion.

[0117] (4) Under the condition of stirring in an oil bath at 80° C., the BNNS aqueous dispersion was added dropwise to the PVA-TA mixed solution in step (2), and stirring was continued for about 30 min until the mixture was uniformly dispersed, thereby obtaining the PVA-TA@BNNS coating.

[0118] (5) After washing the rigid polyurethane foam (RPUF) with ethanol three times, drying and setting aside, 33.3 g of the PVA-TA@BNNS coating prepared in step (4) was applied to the surface of the RPUF, and then placed in an oven at 40° C. until completely cured, obtaining a coating coating amount per unit area of ​​200 g / m 2 Flame retardant polyurethane rigid foam (200-BN-RPUF).

[0119] The flame retardant polyurethane rigid foams obtained in Examples 5, 6 and 7 were tested for flame retardant properties. The test chart can be referred to Fig.10 , Fig.10 The left figure in the figure shows the change of heat release rate (HRR) of the flame retardant polyurethane obtained in Examples 5, 6 and 7 over time. Fig.10 The right figure in the figure shows the change of the total smoke release (TSR) of the flame retardant polyurethane hardness obtained in Examples 5, 6 and 7 over time. Fig.10 It can be seen that after the flame retardant coating of the present invention is prepared on the surface of the polyurethane rigid foam, its heat release rate (HRR) is greatly reduced, and as the density of the flame retardant coating increases, its heat release rate (HRR) gradually decreases. It can be seen that the flame retardant coating of the present invention can greatly improve the flame retardancy of the flame retardant polyurethane rigid foam.

[0120] Fig.11 A in the figure is the SEM image of the carbon layer of pure polyurethane rigid foam after flame retardancy test. Fig.11 B is a SEM image of the flame retardant coating of the flame retardant polyurethane rigid foam prepared in Example 7 after the flame retardant test. The surface of the char layer after the flame retardant treatment is dense and the structure is complete, indicating that the flame retardant coating can form a good thermal insulation barrier on the surface of the flammable material to protect the internal material, thereby improving the fire safety performance of the material.

[0121] Comparative Example 1

[0122] (1) 12.75 g of polyvinyl alcohol (PVA-1788) was dissolved in 115 g of deionized water to prepare a 10% PVA aqueous solution. 6.375 g of tannic acid was added to 227.5 g of ethanol and stirred until completely dissolved.

[0123] (2) Under the condition of stirring in an oil bath at 80° C., the ethanol solution of tannic acid was added dropwise to the PVA aqueous solution, and stirring was continued for about 30 min until the solution was completely dispersed, thereby obtaining a PVA-TA coating.

[0124] (3) After washing the rigid polyurethane foam (RPUF) with ethanol three times, the RPUF was dried for later use. 16.67 g of the PVA-TA coating prepared in step (2) was applied to the surface of the RPUF, and then placed in an oven at 40° C. until completely cured, thereby obtaining a PVA-TA-RPUF coating.

[0125] The flame retardant performance of the flame retardant polyurethane rigid foam (PVA-TA-RPUF) in this comparative example is tested. The test chart can be referred to Fig.10 , Fig.10 The figure shows the change of heat release rate (HRR) of PVA-TA-RPUF over time. Fig. 9 The right figure in the figure shows the change of total smoke release (TSR) of PVA-TA-RPUF over time, Fig. 9 It can be seen that the flame retardancy of the PVA-TA-RPUF obtained by this team is poor.

[0126] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0127] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A flame retardant coating, characterized in that: include: Polymer main agent; Cross-linking agent; A flame retardant, wherein the flame retardant is a functionalized inorganic nanosheet; as well as Dispersion medium.

2. The flame retardant coating according to claim 1, characterized in that: The polymer main agent is polyvinyl alcohol, the cross-linking agent is tannic acid, and the dispersion medium is water and ethanol.

3. The flame retardant coating according to claim 1 or 2, characterized in that: The solid content of the flame retardant coating is 50-60 mg / g.

4. The flame retardant coating according to claim 3, characterized in that: Based on the total mass of solids in the flame retardant coating, the flame retardant coating comprises, by mass percentage: 40% to 50% of the polymer main agent; 20% to 30% of the cross-linking agent; 20% to 30% of the functionalized inorganic nanosheets, Optionally, the dispersion medium is water and ethanol in a volume ratio of 1: (0.5-1.5).

5. The flame retardant coating according to claim 1 or 2, characterized in that: The functionalized inorganic nanosheets are tannic acid-modified inorganic nanosheets.

6. The flame retardant coating according to claim 5, characterized in that: The functionalized inorganic nanosheet has a plane size of 0.2 to 2 μm and a thickness of 5 to 20 nm.

7. The flame retardant coating according to claim 5, characterized in that: The inorganic material in the functionalized inorganic nanosheet is at least one of boron nitride, expanded graphite and mica.

8. The flame retardant coating according to claim 7, characterized in that: The boron nitride is hexagonal boron nitride.

9. A method for preparing the flame retardant coating according to any one of claims 1 to 8, characterized in that: include: Adding a polymer main agent and a cross-linking agent into a dispersion medium respectively to obtain a mixed solution; The functionalized inorganic nanosheets are gradually added to the mixed solution, and stirred evenly at a predetermined temperature to obtain the flame retardant coating.

10. The method according to claim 9, characterized in that The predetermined temperature is 70°C to 90°C.

11. The method according to claim 9 or 10, characterized in that: The preparation method of the functionalized inorganic nanosheet comprises: The inorganic material and tannic acid are uniformly mixed and ball-milled for a predetermined time to obtain a ball-milled mixture; adding a dispersant to the ball-milled mixture to obtain a dispersion; The dispersion liquid is ultrasonicated, centrifuged, cleaned, and dried to obtain the functionalized inorganic nanosheet.

12. The method according to claim 11, characterized in that The mass ratio of the inorganic material to the tannic acid is 1:(1.5-2), Optionally, the predetermined time is 8 to 10 hours.

13. A flame retardant coating, characterized in that: The flame retardant coating is prepared by the flame retardant coating according to any one of claims 1 to 8.

14. The flame retardant coating according to claim 13, characterized in that: The thickness of the flame retardant coating is 50-150 μm.

15. A composite board, characterized in that: include: Base material; The flame retardant coating according to claim 13 or 14, wherein the flame retardant coating is disposed on at least one surface of the substrate, and optionally, the substrate is at least one of polyurethane foam, wood board and polyvinyl chloride board.

16. A method for preparing the composite board according to claim 15, characterized in that: include: Applying the flame retardant coating according to any one of claims 1 to 8 on at least one surface of a substrate; The flame retardant coating is cured at a set temperature to obtain the composite board. Optionally, the set temperature is 35°C to 55°C.

Citation Information

Patent Citations

  • Preparation method of two-dimensional ultrathin boron nitride nanosheet

    CN106744735A

  • Flame-retardant coating and application thereof

    CN107151500A

  • Quantum dot-doped functional boron nitride polymeric heat conducting compound film and preparation method thereof

    CN109181301A

  • Flame-retardant nanocomposite environment-friendly coating and preparation method thereof

    CN111560197A

  • Flame-retardant material with layered brick-wall structure and preparation method of flame-retardant material

    CN113929951A